2015
DOI: 10.1007/s11517-015-1360-1
|View full text |Cite
|
Sign up to set email alerts
|

Identifying relevant group of miRNAs in cancer using fuzzy mutual information

Abstract: MicroRNAs (miRNAs) act as a major biomarker of cancer. All miRNAs in human body are not equally important for cancer identification. We propose a methodology, called FMIMS, which automatically selects the most relevant miRNAs for a particular type of cancer. In FMIMS, miRNAs are initially grouped by using a SVM-based algorithm; then the group with highest relevance is determined and the miRNAs in that group are finally ranked for selection according to their redundancy. Fuzzy mutual information is used in comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Articles reports that miR-519 was involved in the regulation of lung cancer processes. 9,10 Cheng et al 11 reported that knockdown of LINC01419 inhibited cell proliferation and metastasis in lung adenocarcinoma via upregulating miR-519b-3p.…”
Section: Introductionmentioning
confidence: 99%
“…Articles reports that miR-519 was involved in the regulation of lung cancer processes. 9,10 Cheng et al 11 reported that knockdown of LINC01419 inhibited cell proliferation and metastasis in lung adenocarcinoma via upregulating miR-519b-3p.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of these genes and miRNAs have previously been correlated to lung cancer. For example, a suppressed translation and degradation of ULK1 represents a potential mechanism for autophagy limitation in lung cancer [33] , whereas miR-320c was described as core predictor for lung and other cancers [34] .…”
Section: Discussionmentioning
confidence: 99%
“…Certain people have working one cancer Figure 1. Represented the framework of can by using FSs [36,37], BFSs [38,39], and CFSs [40]. Cancer is a collection of diseases in which cells separate without mechanism or order.…”
Section: Introductionmentioning
confidence: 99%